Pengembangan Media Pembelajaran Pop-Up Book Pada Muatan Pembelajaran IPS Kelas IV SDN 07 Kota Bima Tahun Ajaran 2021/2022 - Qurrata A’yun; Nurhasanah Nurhasanah; Moh Irawan Zain (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
The aim of this study is to produce products and find out the feasibility of the media pop-up book that has been developed. The research methods were the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation) and with R&D (Research and Development) research design or known as research and development conducted by a teacher and 6 learners in SDN 07 Bima City. The object of this research is a media pop-up book IPS (Social Science) content, theme